Identifying breast cancer patients who gain the most dosimetric benefit from deep inspiration breath hold radiotherapy. Issue 4 (5th July 2020) - Browne, Patricia; Beaton, Nakia‐Rae; Sharma, Harish; Watson, Sharon; Mai, G Tao; Harvey, Jennifer; Bernard, Anne; Brown, Elizabeth; Hargrave, Catriona; Lehman, Margot
Abstract: Introduction: Deep inspiration breath hold (DIBH) has been proven to reduce cardiac dose for women receiving left breast and chest wall radiation therapy. However, it utilises extra departmental resources and patient exertion. The aim of this exploratory study was to investigate if any factors existed that could identify breast cancer patients who may benefit most from DIBH, to facilitate appropriate utilisation of departmental resources. Methods: Left‐sided breast cancer patients aged 18–70 years, and right‐sided breast cancer patients with internal mammary nodes included, were recruited. DIBH and free breathing (FB) plans were created for all patients. Patient demographic and clinical history were recorded. Variables including lung threshold value, lung volume, patient separation, maximum heart in field, volume of planning target volume (PTV), heart dose, ipsilateral lung dose were compared between plans. Results: Plans for 31 patients were analysed. No correlations were found between lung threshold value or patient separation and cardiac dose. Moderate to strong correlations were found with BMI, PTV volume and lung volume change however no definitive thresholds were determined. A significant difference was found in the maximum heart in field between DIBH and FB ( P < 0.001) with those patients with greater than 0.7 cm heart in the field on the FB scan demonstrating greater reductions in mean heart dose. Conclusion: Maximum heart in the field of greater than 0.7 cm in FB could be a potential factor to identify patients who may benefit most from DIBH. This factor warrants investigation in a larger patient cohort to test its validity. Abstract : The aim of this study was to investigate factors that could help identify breast cancer patients who may benefit most from DIBH, to facilitate appropriate utilisation of departmental resources. Only factors that could be evaluated after CT simulation were found to have a significant relationship with reduction in heart dose. The only possible threshold identified was the maximum heart in field in free breathing, with those patients with >0.7 cm heart in field experiencing greater reductions in mean heart dose.